Optimal conditions for the covalent immobilization of lipase from Candida rugosa for the production of biodiesel - Supaluk Tantong (Chulalongkorn University, 2008)
Biodiesel (fatty acid alkyl ester) is an alternative fuel which is biodegradable, non- toxic and environmental friendly. Recently, lipase catalyzed transesterification has attracted more attention for biodiesel production because of higher purity product and easy separation of biodiesel from the byproduct, glycerol. However, the cost of enzyme remains a barrier for its industrial implementation. Enzyme immobilization provides considerable increase in efficiency and covalent immobilization has been recognized as the method that yields more stability to the enzyme than adsorption. Hence, the aim of this work is to optimize the conditions for the covalent immobilization of Candida rugosa lipase (CRL), which is one of the most frequently used enzymes for industrial applications on the epoxy enzyme carriers, Sepabeads ECHFA. Firstly, the various optimal conditions for the immobilization were investigated. The results were as follows: pH 8, 1.25 M ionic strength, 8 mg/ml enzyme loading at 20 oC for 5 hours, 0.5% (v/v) tween-80 as adjuvant and blocking with 1M glycine for 10 hours. Then, the optimal substrates for transesterification were screened from 14 types of edible plant oils. Seven of edible plant oils showed potential as feedstocks suitable for biodiesel production from their physical properties and the yield of transesterification catalyzed by commercial lipases; Novozyme® 435 and Lipozyme® RMIM. Nevertheless, palm oil represented the most suitable raw material considering the climatic and cultivation conditions. The optimal conditions for the production of biodiesel by transesterification using palm oil as the substrate were determined. The results were: 4 steps additional mode of methanol, three to one molar ratio of methanol to palm oil, 15% of oil by weight, enzyme loading at 40 oC for 12 hours with no additional water required. From these optimal conditions, biodiesel production was 67%. When the above two commercial immobilized lipases were applied to catalyze the reaction under the same condition, 72% and 60% fatty acid methyl esters were obtained from Novozyme® 435 and Lipozyme® RMIM respectively. Finally, the immobilized Candida rugosa lipases were tested for the reusability in both transesterification and hydrolysis. Unfortunately, the immobilized CRL could not be reused after single catalysis of transesterification. However, its hydrolytic activity appeared considerably well maintained up to the 4th cycle. Overall results indicated that biodiesel could be produced by the Candida rugosa lipase covalently immobilized on Sepabeads EC-HFA.